Growth, yield and nutritional composition of moringa oleifera under different propagation methods - Mahlangu, Nelisiwe (My University, 2024)
Moringa oleifera, often referred to as the "drumstick tree" or "miracle tree," has gained prominence for its nutritional and medicinal properties. This study aimed to assess the impact of different propagation methods on the growth, yield and nutritional composition of Moringa oleifera and recommending the best method that can be used for propagating the tree. Three propagation techniques, including direct seeding, stem cuttings, and seedling transplanting, were investigated. This research was carried out at the University of Limpopo Aquaculture Research Unit (ARU), located in Mankweng area, Limpopo Province, South Africa. The growth parameters, including emergence, sprouting, and rooting rates, height of the shoots, number of branches per plant, stem diameter, and chlorophyll content, were monitored at three weeks intervals. Additionally, yield components such as fresh and dry weight of the shoots and roots were quantified. Nutritional composition, proximate composition encompassing macro and micronutrients, was analyzed in harvested plant leaves. Results indicated that seedling transplanting-propagated plants exhibited the highest initial growth rates, while cuttings and direct seeding plants displayed slower but consistent growth. However, significant variations in yield were observed, with seedling transplanted plants demonstrating higher fresh shoot and root weight and higher dry shoot and root weight. Nutritional analysis revealed subtle differences in the composition of leaves among the propagation methods, with implications for the overall nutritional quality of harvested products. The findings of this study contribute valuable insights into the cultivation practices of Moringa oleifera, providing information on the most effective propagation methods for desired outcomes in terms of growth, yield, and nutritional composition. This knowledge can aid farmers, researchers, and policymakers in optimizing Moringa oleifera cultivation for enhanced nutritional benefits and sustainable agricultural practices.
Thesis (M. Sc. (Agronomy)) -- University of Limpopo, 2024
Keywords: Growth parameters; Moringa oleifera; Nutritional composition; Propagation methods; Sustainable agriculture; Yield components; Moringa oleifera; Plant propagation